Palestinian Social Political Conflict in Mourid Barghouti’s Novel Ra’aytu Ramallah: A Ralf Dahrendorf’s Perspective - Dinia, Hima Roiku (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2024)
PurposeThis study aimed to determine the forms of socio-political conflict in the novel Ra'aytu Ramallah by Mourid Barghouti based on the perspective of Ralf Dahrendorf; and describe and classify the conflict based on the two faces of society, power and authority, groups involved in the conflict, and conflict control. MethodThis descriptive qualitative research used Ralf Dahrendorf's theory to describe socio-political conflict in Mourid Barghouti's novel Ra'aytu Ramallah. This study used Mourid Barghouti's novel Ra'aytu Ramallah. It used a reading and note-taking to collect data on socio-political tensions in Mourid Barghouti's novel Ra'aytu Ramallah from Ralf Dahrendorf's perspective, while its analysis used Miles and Hubberman's interactive model analysis that has three stages: data reduction, data presentation, and conclusion. Result/FindingThe results of this study showed this conflict consisted of several forms, namely the struggle for settlements, attacks by the Intifada movement, and social conflicts that occur within the Palestinian community itself. In conflict and consensus, there were three forms of conflicts and two forms of consensus. Between the two sides in the conflict, power was dominated by the Israeli side. There are one form of power and two forms of authority. In the parties involving in the conflict, there were two quasi groups and two interest groups. In an effort to control conflicts, there was one form of arbitration. ConclusionThe socio-political conflict in the novel Ra'aytu Ramallah by Mourid Barghouti is in the form of a power struggle conflict that occurs between Palestine and Israel. This conflict takes several forms, namely the struggle for forced settlements by Israel against the Palestinians, the attacks carried out by the Intifada as a form of resistance to the Israeli occupation, and the social conflicts that occur within Palestinian society itself between Palestinians who work with Israel and its loyal Palestinian population are fighting against Israel for the sovereignty of its state.